Health profile of primary school students: a cross sectional study among urban and rural areas of eastern Haryana - Singh, Mahender; Choudhary, Diksha; Tak, Himani; Aggarwal, Satish Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Healthy children are the foundation for a healthy nation and nation’s future depends on the status of the children. School Health Program aims to strengthen health promotion and disease prevention intervention. Objective was to assess the health status of primary school students in urban and rural areas of Panipat, Haryana. Methods: This school based cross sectional study was conducted in the urban and rural field practice areas of community medicine department, NCMCH, Panipat during February-March 2023. Convenience sampling was adopted to select primary schools from 1st to 5th standard. A semi-structured proforma was used to record information regarding anthropometric measurements, physical examination, clinical findings etc. Results: Total 261 primary school students were examined. Most common morbidity identified was ENT problems (ear wax, ear discharge) in both urban (80%) and rural (50%) students. Poor personal hygiene was observed in 1/5th students. Skin problems, refractory errors, micronutrient deficiency and respiratory problems were also identified. Difference between the nutritional status in urban and rural students was found to be statistically significant. Conclusions: The common health problems found in children such as ear discharge, anaemia, poor personal hygiene and undernutrition can be addressed with implementation of school health programme in effective way.